Caracterización de los semilleros de investigación en los programas de contaduría pública en Colombia (2016)
This article was developed from the interest to know the aspects that identify the seedbeds of the faculties of public accounting in the country, regarding its members, research lines, productivity, financing and training. A sample of the academic programs at national level was taken as basis, and a quantitative and qualitative methodological approach was used, through two models of surveys addressed to teachers and students. This allowed us to identify the main features of a total of twenty active research seedbeds.